Influence of E. coli strain Nissle 1917 (EcN) on intestinal gas dynamics and abdominal sensation - Hernando-Harder, Ana C.; von Bünau, Rudolf; Nadarajah, Mahaluxmy; Singer, Manfred V.; Harder, Hermann (Digestive diseases and sciences, 2008)
E. coli strain Nissle 1917 (EcN) is a probiotic clinically used with various indications. However, especially at the beginning of treatment, some patients report abdominal bloating. In a prospective, randomized, double-blind study in 30 healthy individuals we assessed the influences of EcN on intestinal gas dynamics and abdominal sensation. After one week without medication volunteers orally received 2.5-25 × 109 colony-forming units of EcN or placebo per day for 21 days. EcN was well tolerated and did not significantly affect abdominal symptoms, stool frequency or stool consistency. During gas challenge at different days no difference in the perception scores (range from 0 = no perception to 6 = pain) was observed between the two groups: the mean perception score was 1.2 (SD 0.2) in the EcN group and 1.4 (SD 0.2) in the placebo group. EcN had no relevant influence on intestinal gas dynamics.